Exploring the economic impact of a pandemic on gig employment: a case of e-hailing taxi drivers in Sabah - Khairul Hanim Pazim; Kasim Mansur; Noor Fzlinda Fabeil; James Alin; Roslinah Mahmud (Universiti Malaysia Sabah, 2020)
Recently, the world has been experiencing some of the common contagious diseases, the COVID-19. The WHO has declared a pandemic following the spread of the disease involving 210 countries reaching 2 million cases. As a result, all non-essential economic activities are halted. Similar to other countries, Malaysia had implemented movement control and border control in the effort to curb the virus from spreading. The outbreak has indeed disrupted most economic sector, including the tourism industry. The viral outbreak had forced countries to implement travel bans and restrictions, resulting in a 6% tourist arrival decrease in Malaysia by March 2020, as reported by Statistica Research Department (2020). Local people, too, are asked to obey the social distancing and isolation urging them to stay at home. As travel is restricted, the impact is most felt among those providing mobility services, such as ride-hailing and taxi services. Their work has been disrupted during the crisis due to a loss of demand from clients and passengers, as well as the health risk associated with the spread of the virus. The sluggish market caused by the pandemic is expected to last for several months. Thus, lower-income, budget constraint, reduced spending power and inadequate preparedness for an emergency make it impossible for e-hailing taxi drivers to survive.